Scale-up of the electrokinetic fence technology for the removal of pesticides. Part II: Does size matter for removal of herbicides?. (January 2017) - López-Vizcaíno, R.; Risco, C.; Isidro, J.; Rodrigo, S.; Saez, C.; Cañizares, P.; Navarro, V.; Rodrigo, M.A.
Abstract: This work reports results of the application of electrokinetic fence technology in a 32 m 3 -prototype which contains soil polluted with 2, 4-D and oxyfluorfen, focusing on the evaluation of the mechanisms that describe the removal of these two herbicides and comparing results to those obtained in smaller plants: a pilot-scale mockup (175 L) and a lab-scale soil column (1 L). Results show that electric heating of soil (coupled with the increase in the volatility) is the key to explain the removal of pollutants in the largest scale facility while electrokinetic transport processes are the primary mechanisms that explain the removal of herbicides in the lab-scale plant. 2-D and 3-D maps of the temperature and pollutant concentrations are used in the discussion of results trying to give light about the mechanisms and about how the size of the setup can lead to different conclusions, despite the same processes are occurring in the soil. Graphical abstract: Highlights: Facility size matters in the mechanisms that explain removal of herbicides from soil. Electric heating of soil is the key to explain the remediation in the prototype. Electrokinetic transport processes becomes more important as the size of the setup decreases. Volatilization is the main mechanisms that explain the removal of 2, 4-D and oxyfluorfen.